Methods of treatment pulp diseases. Modern aspects in clinical practice (LLC "Endo Press", 2020)
Despite the usefulness of the biological treatment of pulpitis, especially in the early stages of the disease process or accidental opening of the tooth cavity of different age groups of patients without burdening somatic diseases, this method doesn't occupy a dominant position among the other kinds of treatment of pulpitis. It has been shown that a relatively wide spread of devices for ozone therapy in modern dental clinics creates favorable prospects for the introduction of the dental practice, developed at the Department of Therapeutic Dentistry RNIMU of NI Pirogov, the method of treatment of reversible forms of pulpitis using ozone therapy in combination with direct pulp capping with medical materials.